Rearing five species of Diptera (Calliphoridae) of forensic importance in Colombia in semicontrolled field conditions - Vélez, María C. (2008)
The family Calliphoridae is widely known to lead the colonization of corpses and their development rates are frequently used to estimate the postmortem interval. This study presents the larval growth of five forensically important species of Calliphoridae in Colombia. Rearing took place in semicontrolled field conditions where the egg masses were collected. We show curves of larval growth, larval length and time intervals to reach all immature stages for Lucilia eximia and Cochliomyia macellaria at two sites with different climatic conditions and for Chrysomya albiceps, Chrysomya megacephala and Calliphora nigribasis at one site. Overall, high temperatures speeded up the development of the species reared at two different sites, whereas low temperatures for C. nigribasis, lengthened the total development time. Differences between this study and others can be explained by the experimental conditions in the field without the possibility of strict laboratory rearing controls.